Hemodynamic characteristics and clinical treatment of patients with iliac vein compression syndrome - Shi, Beihao; Huang, Linchen; Wei, Sen; Zhu, Jian; Li, Zhiwei; Ren, Jie; Chen, Dian (Frontiers in Surgery, 2025)
Iliac vein compression syndrome (IVCS), also known as May–Thurner syndrome or Cockett syndrome, refers to the compression of the iliac veins by surrounding tissues, typically the compression of the left iliac vein by the right iliac artery anteriorly and the vertebral body posteriorly. A narrowed iliac vein leads to a series of hemodynamic changes that can affect the function of the vascular endothelium and create an environment prone to thrombosis. These hemodynamic parameters can guide stent placement and aid in diagnosing IVCS. This article also summarizes existing methods for the hemodynamic assessment of IVCS and suggests potential future research directions by drawing on the more mature field of arterial hemodynamics.